Engaged Reading: Moving from Theory to Implication for L2 Learners - Selim, Sheikh Mohammad Masud; Islam, A B M Shafiqul (JOLLT Journal of Languages and Language Teaching, 2022)
There have been a good number of research studies on ‘engaged reading’ in general but not much literature is known about the ‘engaged reading’ that makes connections between theory and practice with special reference to ESL/EFL teachers. Hence, this paper aims to examine the efficacy of engaged reading and shows how it can be facilitated through mass awareness among the ESL or EFL teachers. Teachers’ adequate knowledge and perception about engaged reading can only ensure the implementation of it as a means of learning by owning the language thus creating a real attachment to it. This article uses a qualitative research method that exclusively uses the relevant secondary references/works available on the topic. The literature revealed that attitudes and strategy instruction of teachers in the classroom play a significant role in terms of increasing the learners’ motivation for reading with interest and their reading engagement for better academic achievement. The paper finally demonstrates how teachers with the best of their potential and concentration can immensely contribute to the growth of a reader to be an engaged reader.